Preparation method of modified hexagonal boron nitride filler
The surface modification of hexagonal boron nitride through sol-gel reaction and chemical grafting methods solves the problems of poor wetting and clustering in the coating system, and achieves uniform dispersion and high-performance application of modified hexagonal boron nitride fillers in the coating.
Patent Information
- Application Number
- CN202411803892.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
Hexagonal boron nitride is prone to clustering in coating systems, has poor wettability, and the traditional modification methods are complex and expensive, which affects its application in coatings.
Hexagonal boron nitride is surface modified through sol-gel reaction and chemical grafting, and materials such as silicon sol and uruol are used to enhance their surface wettability and corrosion resistance.
The surface wetting and corrosion resistance of hexagonal boron nitride filler is improved, making it evenly dispersed in the coating, and enhancing the corrosion resistance and thermal conductivity of the coating.
Smart Images

Figure CN119592100A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite functional fillers, and particularly relates to a preparation method of modified hexagonal boron nitride fillers. Background Art
[0002] The addition of fillers has a significant impact on the performance of coatings, including improving mechanical properties, anti-corrosion properties, thermal stability, improving rheological properties and optical properties, reducing costs, and enhancing chemical properties. Fillers of different types and characteristics have a variety of effects on coating performance. By carefully optimizing and selecting inorganic fillers, the application performance of coatings can be specifically improved to meet the needs of different fields.
[0003] Due to its unique physical and chemical properties, hexagonal boron nitride is a relatively high-end functional inorganic filler. Its doping in coatings can give the coatings good high-temperature stability, wear resistance, corrosion resistance, thermal conductivity, electrical insulation, lubricity, non-wetting and other properties. However, due to the passivation characteristics of the surface of hexagonal boron nitride and poor wettability, it is easy to cluster when doped in the coating system. Hexagonal boron nitride only achieves metal protection in the coating system by forming a maze effect in the coating through physical barriers. In addition, the application of boron nitride coatings may require specific techniques and equipment to ensure the uniformity and adhesion of the coating, and the coatings with boron nitride need to be stored under specific temperature and humidity conditions to maintain their performance. Therefore, boron nitride needs to be modified by stripping or surface modification to optimize its application in coatings. However, traditional modification methods are more complicated and costly. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a modified hexagonal boron nitride filler, which takes hexagonal boron nitride as a matrix and modifies its surface. While enhancing its surface wettability, its anti-corrosion performance is improved by enriching chemical substances with corrosion inhibition effect on the surface, so that it can be used in the field of functional coatings with both anti-corrosion and thermal conductivity properties.
[0005] In order to achieve the above technical effects, the technical solution adopted by the present invention is: A method for preparing a modified hexagonal boron nitride filler comprises the following preparation steps: Step 1: Add a wetting dispersant to the ethanol solvent and mix well. Then slowly add the hexagonal boron nitride powder at a speed of 200 to 500 rpm. After mixing well, ultrasonically disperse for 1 to 3 hours to fully mix and disperse evenly.
[0006] Step 2: gradually heat the mixture obtained in step 1 to 30°C to 50°C, drip phosphoric acid, adjust the pH value of the system to about 3-4, and gradually drip a mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and control the dripping time to be 3 to 6 hours. After the dripping is completed, control the temperature to 40°C to 60°C, continue the reaction for 12 to 72 hours, and grow a covering silica sol on the surface of hexagonal boron nitride through a sol-gel reaction.
[0007] Step 3: Add urushiol and initiator to the system product obtained in step 2, mix well, stir and heat to 60°C to 70°C, react for 12 to 36 hours, and then cool to room temperature.
[0008] Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 80° C. to 100° C. under vacuum for 12 to 24 hours; after grinding and sieving, a modified hexagonal boron nitride filler is obtained.
[0009] Preferably, the concentration of the hexagonal boron nitride powder in ethanol in step 1 is controlled at 6 g / ml to 20 g / ml.
[0010] Preferably, the particle size of the hexagonal boron nitride powder in step 1 ranges from 5 microns to 30 microns.
[0011] Preferably, the wetting and dispersing agent used in step one may be a nonionic wetting and dispersing agent, specifically polyol polyoxyethylene ether fatty acid ester, polyoxyethylene ether, or alkylphenol polyoxyethylene ether.
[0012] Preferably, in the mixture added dropwise in step 2, the mass ratio of ethyl orthosilicate to γ-methacryloxypropyltrimethoxysilane is in the range of 90:10 to 99:1.
[0013] Preferably, the initiator used in step three can be azobisisobutyronitrile, azobisisoheptanenitrile, or dimethyl azobisisobutyrate.
[0014] A modified hexagonal boron nitride filler is prepared by the above-mentioned preparation method and can be added into a polymer resin to prepare a composite coating for application in the field of coating protection.
[0015] 1. The surface of boron nitride is modified by sol-gel reaction and chemical grafting. The operation process is simple, the environmental performance is good, and it will not cause any harm.
[0016] 2. The silica sol with corrosion inhibitor wraps the boron nitride. Since the surface of the acidic silica sol carries more silanol groups, its surface has good adhesion, strong adhesion, good permeability and good dispersibility. It can effectively modify the surface of the boron nitride filler and improve the surface wettability of the filler, which is beneficial to the uniform dispersion of the prepared composite filler in the coating system.
[0017] 3. The effective combination of lacquer phenol makes the prepared composite coating have corrosion inhibition effect and improves the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The modified hexagonal boron nitride filler prepared in Example 1 observed by scanning electron microscopy; Figure 2 The cross-sectional morphology of the cured coating of the modified hexagonal boron nitride filler prepared in Example 1 is obtained by scanning electron microscopy; DETAILED DESCRIPTION Example
[0019] A method for preparing a modified hexagonal boron nitride filler comprises the following preparation steps: Step 1: Add a wetting and dispersing agent to the ethanol solvent, mix evenly, then slowly add the hexagonal boron nitride powder at a speed of 200 rpm, and after mixing evenly, ultrasonically disperse for 3 hours to fully mix and disperse evenly. The particle size of the hexagonal boron nitride powder is 29 to 30 microns, and its concentration in ethanol is controlled at 20g / ml. The wetting and dispersing agent used is a non-ionic wetting and dispersing agent polyol polyoxyethylene ether fatty acid ester.
[0020] Step 2: gradually heat the mixture of step 1 to 30°C, drip phosphoric acid, adjust the pH value of the system to about 3, and gradually drip a mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and control the dripping time to 6 hours. After the dripping is completed, the temperature is controlled at 40°C, and the reaction is continued for 72 hours. Through the sol-gel reaction, a silica sol is grown on the surface of hexagonal boron nitride. Among them, the mass ratio between ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane used is in the range of 90:10.
[0021] Step 3: Add urushiol and initiator azobisisobutyronitrile to the product of step 2, mix well, stir and heat to 60° C., react for 36 hours, and then cool to room temperature.
[0022] Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 80° C. under vacuum for 24 hours. After grinding and sieving, a modified hexagonal boron nitride filler is obtained. Example
[0023] A method for preparing a modified hexagonal boron nitride filler, characterized in that it comprises the following preparation process steps: Step 1: Add a wetting and dispersing agent to the ethanol solvent, mix well, and then slowly add hexagonal boron nitride powder at a speed of 300 rpm. After being evenly mixed, ultrasonically disperse for 2.5 hours to fully mix and disperse evenly. The particle size range of the hexagonal boron nitride powder is 20±1 microns, and its concentration in ethanol is controlled at 15g / ml. The wetting and dispersing agent used is a non-ionic wetting and dispersing agent polyoxyethylene ether.
[0024] Step 2: gradually heat the mixture of step 1 to 35°C, drip phosphoric acid, adjust the pH value of the system to about 3, and gradually drip a mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and control the dripping time to 5 hours. After the dripping is completed, the temperature is controlled at 55°C, and the reaction is continued for 60 hours. Through the sol-gel reaction, a silica sol is grown on the surface of hexagonal boron nitride. Among them, the mass ratio between ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane used is in the range of 92:8.
[0025] Step 3: Add urushiol and initiator azobisisoheptanenitrile to the product of step 2, mix well, stir and heat to 63° C., react for 30 hours, and then cool to room temperature.
[0026] Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 85° C. under vacuum for 20 hours. After grinding and sieving, a modified hexagonal boron nitride filler is obtained. Example
[0027] A method for preparing a modified hexagonal boron nitride filler, characterized in that it comprises the following preparation process steps: Step 1: Add a wetting and dispersing agent to the ethanol solvent, mix well, and then slowly add hexagonal boron nitride powder at a speed of 400 rpm. After being evenly mixed, ultrasonic dispersion is performed for 2.5 hours to fully mix and disperse evenly. Wherein, the particle size range of the hexagonal boron nitride powder is 10±1 microns, and its concentration in ethanol is controlled at 10g / ml. The wetting and dispersing agent used is a nonionic wetting and dispersing agent alkylphenol polyoxyethylene ether.
[0028] Step 2: gradually heat the mixture of step 1 to 45°C, drip phosphoric acid, adjust the pH value of the system to about 3.5, and gradually drip the mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and control the dripping time to 4 hours. After the dripping is completed, the temperature is controlled at 45°C, and the reaction is continued for 24 hours. Through the sol-gel reaction, silica sol is grown on the surface of hexagonal boron nitride. Among them, the mass ratio between ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane used is in the range of 95:5.
[0029] Step 3: Add urushiol and initiator dimethyl azobisisobutyrate to the product of step 2, mix well, stir and heat to 65° C., react for 24 hours, and then cool to room temperature.
[0030] Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 95° C. for 15 hours under vacuum. After grinding and sieving, a modified hexagonal boron nitride filler is obtained. Example
[0031] A method for preparing a modified hexagonal boron nitride filler, characterized in that it comprises the following preparation process steps: Step 1: Add a wetting and dispersing agent to the ethanol solvent, mix well, and then slowly add the hexagonal boron nitride powder at a speed of 500 rpm. After being mixed evenly, ultrasonically disperse for 2.5 hours to fully mix and disperse evenly. The particle size of the hexagonal boron nitride powder is 5 to 6 microns, and its concentration in ethanol is controlled at 6g / ml. The wetting and dispersing agent used can be a non-ionic wetting and dispersing agent polyol polyoxyethylene ether fatty acid ester.
[0032] Step 2: gradually heat the mixture of step 1 to 50°C, drip phosphoric acid, adjust the pH value of the system to about 4, and gradually drip the mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and control the dripping time to 3 hours. After the dripping is completed, the temperature is controlled at 60°C, and the reaction is continued for 12 hours. Through the sol-gel reaction, silica sol is grown on the surface of hexagonal boron nitride. Among them, the mass ratio between ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane used is in the range of 99:1.
[0033] Step 3: Add urushiol and initiator azobisisoheptanenitrile to the product of step 2, mix well, stir and heat to 70° C., react for 12 hours, and then cool to room temperature.
[0034] Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 100° C. for 12 hours under vacuum. After grinding and sieving, a modified hexagonal boron nitride filler is obtained.
[0035] According to the raw material ratio shown in Table 1, a coating doped with the filler prepared by the present invention was prepared.
[0036] Table 1. Paint preparation scheme of the composite filler prepared according to the present invention raw materials w / % Modified hexagonal boron nitride fillers prepared in Examples 1 to 4 30 Bentonite thickener 2 Epoxy resin (epoxy value 0.20mol / 100g) 25 Polyamide curing agent 651 15 Xylene 20.5 Butyl acetate 7 Defoaming agent 0.2 Leveling agent 0.2 Wetting and dispersing agents 0.1 The bentonite thickener is BENTONE SD-1 from Hemmings, the defoamer can be BYK-070 and BYK-8800 from BYK, or TEGO® Foamex N from Digo. The leveling agent can be BYK-333 from BYK. The wetting and dispersing agent can be A-5088 and A-5044 from Aifka.
[0037] The preparation scheme is as follows: first, melt the epoxy resin at 80°C, then add it to xylene with a wetting dispersant, stir at 1500 rpm for 10 minutes, and dissolve and stir evenly. Then gradually add the composite filler prepared by the present invention, stir at 1800 rpm for 2 hours, then add the leveling agent, defoamer and butyl acetate solvent, stir at 500 rpm for 15 minutes, and mix evenly. Before coating the board, add the polyamide curing agent 651 designed in Table 1, stir evenly to obtain the designed composite coating, and each coating is correspondingly defined as Example 1 coating, Example 2 coating, Example 3 coating, and Example 4 coating. It is applied to the surface of the metal substrate by brushing, spraying or rolling, and is left at room temperature for 7 days to test its various properties.
[0038] In addition, in order to compare the actual application effect of the prepared modified hexagonal boron nitride filler, the present invention also selects the hexagonal boron nitride used in Example 1, and prepares a composite coating according to the experimental formula and operating precautions shown in Table 1, which is defined as a comparative example coating.
[0039] The specific performance indicators of the coating prepared by the composite filler prepared by the present invention and the coating prepared by the comparative example coating are shown in Table 2 below: Table 2. Performance indicators of composite coatings and their cured coatings Test items and standards Example 1 Coating Example 2 Coating Example 3 Coating Example 4 Coating Comparative Example 1 Coating State of paint in container After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps Paint drying time (surface drying) / h <2 <2 <2 <2 <2 Paint drying time (actual drying) / h <24 <24 <24 <24 <24 Initial drying crack resistance of coating No cracks No cracks No cracks No cracks No cracks Coating pencil hardness (GB / T 6739-2006) 2H 2H B 2H 2H Coating flexibility (GB / T 1731-1993) 1mm 1mm 1mm 1mm 1mm Cross-cut adhesion of coatings (GB / T 9286-1998) Level 0 Level 0 Level 0 Level 0 Level 0 Impact resistance of coating film (GB / T1732-1993) Forward / reverse flush Forward / reverse flush Forward / reverse flush Forward / reverse flush Forward / reverse flush <![CDATA[Coating through-surface (K ⊥ ) Thermal conductivity]]> 0.46 0.40 0.35 0.35 0.17 <![CDATA[Coating parallel plane (K ∥ ) Thermal conductivity]]> 0.76 0.48 0.56 0.45 0.25 Salt spray resistance of coating (ASTM B117) >300h No blistering, obvious deterioration or softening of the coating >300h No blistering, obvious deterioration or softening of the coating >300h No blistering, obvious deterioration or softening of the coating >300h No blistering, obvious deterioration or softening of the coating >200h No blistering, obvious deterioration or softening of the coating Coating moisture and heat resistance / h (GB / T 1740-2007) 500, no delamination or shedding 500, no delamination or shedding 500, no delamination or shedding 500, no delamination or shedding 300, no delamination or shedding Figure 1 The modified hexagonal boron nitride filler prepared in Example 1 is observed by scanning electron microscopy. The silica sol obtained by sol-gel reaction effectively covers the modified hexagonal boron nitride, and the surface is rough and uneven; this is conducive to promoting the effective dispersion of the filler in the resin. In addition, this concave-convex structure is conducive to the grafting and adsorption of urushiol on the surface of the filler, modifying it, and improving the corrosion resistance of the coating.
[0040] Figure 2 The cross-sectional morphology of the cured coating of the modified hexagonal boron nitride filler prepared in Example 1 is shown by scanning electron microscopy. Due to the modification of the filler surface, it can be evenly dispersed in the coating. On the one hand, a maze effect is formed to inhibit the occurrence of corrosion; on the other hand, the fillers are dispersed and contacted with each other, which is also conducive to forming an effective heat conduction channel.
[0041] The present invention is not limited to the above-mentioned specific implementation modes. For ordinary technicians in this field, various changes made based on the above-mentioned conception without creative work all fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified hexagonal boron nitride filler, characterized in that: The method comprises the following preparation steps: Step 1: Add a wetting dispersant to the ethanol solvent and mix well. Then slowly add the hexagonal boron nitride powder at a speed of 200 to 500 rpm. After mixing well, perform ultrasonic dispersion for 1 to 3 hours to fully mix and disperse well. Step 2, gradually heating the mixture prepared in step 1 to 30°C to 50°C, dropping phosphoric acid, adjusting the pH value of the system to 3-4, and gradually dropping a mixture of ethyl orthosilicate and γ-methacryloxypropyltrimethoxysilane, and controlling the dropping time to 3-6 hours; after the dropping is completed, controlling the temperature to 40°C to 60°C, continuing the reaction for 12-72 hours, and growing a covering silica sol on the surface of hexagonal boron nitride through a sol-gel reaction; Step 3: Add urushiol and initiator to the system product obtained in step 2, mix well, stir and heat to 60°C to 70°C, react for 12 to 36 hours, and then cool to room temperature; Step 4: After filtering, the product of step 3 is repeatedly washed three times with anhydrous alcohol, filtered, and dried at 80° C. to 100° C. under vacuum for 12 to 24 hours; after grinding and sieving, a modified hexagonal boron nitride filler is obtained.
2. The preparation method according to claim 1, characterized in that: The concentration of the hexagonal boron nitride powder in ethanol in step 1 is 6 g / ml to 20 g / ml.
3. The preparation method according to claim 1, characterized in that: The particle size of the hexagonal boron nitride powder in step 1 ranges from 5 microns to 30 microns.
4. The preparation method according to claim 1, characterized in that: The wetting and dispersing agent used in step 1 is a nonionic wetting and dispersing agent.
5. The preparation method according to claim 4, characterized in that: The wetting and dispersing agent is polyol polyoxyethylene ether fatty acid ester, polyoxyethylene ether nonionic surfactant or alkylphenol polyoxyethylene ether.
6. The preparation method according to claim 1, characterized in that: The mass ratio of ethyl orthosilicate to γ-methacryloxypropyltrimethoxysilane in the mixture added dropwise in step 2 is in the range of 90:10 to 99:
1.
7. The preparation method according to claim 1, characterized in that: The initiator used in step 3 is azobisisobutyronitrile, azobisisoheptanenitrile, or dimethyl azobisisobutyrate.
8. A modified hexagonal boron nitride filler, characterized in that: The modified hexagonal boron nitride filler is prepared by the preparation method described in claim 1.